The Serangan Culinary Businesses Learning Video Based on Tri Hita Karana in Social Subject for Fifth Grade Elementary School - Ni Kadek Dila Maharani (International Journal of Elementary Education, 2024)
The lack of instructional media used in the teaching and learning process reduces students' motivation, enthusiasm, and interest in learning. This can impact students' learning outcomes, particularly in social studies (IPS). This research employed a development study using both qualitative and quantitative methods based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were fifth-grade elementary school students.The research resulted in the design and development of a learning video about the Serangan culinary business based on Tri Hita Karana, which was proven to be suitable for use in the fifth-grade learning process. The quality of the learning video about the Serangan culinary business based on Tri Hita Karana was deemed appropriate based on expert reviews (subject content, design, and media), student responses, and the effectiveness of the video. The effectiveness was demonstrated through a t-test using dependent samples, yielding a t-value (tₕ) of 17.901, while the critical tvalue (tₜ) at a significance level of 5% with degrees of freedom (df = n-1 = 24-1 = 23) was 1.713. These results indicate that tcount > ttable leading to the rejection of H₀ and acceptance of H. Thus, it can be concluded that the learning video about the Serangan culinary business based on Tri Hita Karana is effective for teaching the topic of economic conditions in my region in social studies for fifth-grade students. The implications of this research are expected to enhance learning outcomes in social studies and introduce the economic conditions of the Serangan culinary business based on Tri Hita Karana.